The use of multidirectional cross-sectional tomography for localizing an odontome - JOANNA JOHNSON, ERIC J. WHAITES, & EVELYN C. SHEEHY (IAPD and Blackwell, 2007)
Odontomes are hamartomatous developmental malformations of dental hard tissues. They can be differentiated into compound and complex forms.